The Autonomic Nervous System Pulls the Strings to Coordinate Circadian HSC Functions - García-García, Andrés; Méndez-Ferrer, Simón (Frontiers in Immunology, 2020)
As for many other adult stem cells, the behavior of hematopoietic stem and progenitor cells (HSPCs) is subjected to circadian regulatory patterns. Multiple HSPC functions, such as proliferation, differentiation or trafficking exhibit time-dependent patterns that require a tight coordination to ensure daily blood cell production. The autonomic nervous system, together with circulating hormones, relay circadian signals from the central clock – the suprachiasmatic nucleus in the brain – to synchronize HSC niche physiology according to light/darkness cycles. Research over the last 20 years has revealed how specific neural signals modulate certain aspects of circadian HSC biology. However, only recently some studies have started to decipher the cellular and molecular mechanisms that orchestrate this complex regulation in a time-dependent fashion. Here we firstly review some of the recent key findings illustrating how different neural signals (catecholaminergic or cholinergic) regulate circadian HSC egress, homing, maintenance, proliferation and differentiation. In particular, we highlight the critical role of different neurotransmitter receptors in the bone marrow microenvironment to channel these neural signals and regulate antagonistic processes according to circadian cues and organismal demands. Then, we discuss the potential biological meaning of HSC circadian regulation and its possible utility for clinical purposes. Finally, we offer our perspective on emerging concepts in HSC chronobiology.